The Singleness of Increasing the Involvement of the Deaf into Decision-Making in Municipalities in the Republic of Lithuania - Liukinevičienė, Laima; Kvietkienė, Evelina (Socialiniai tyrimai, 2014)
Surveys implemented in the municipalities of the biggest Lithuanian cities in 2013-2014 have indicated the main reasons for the insufficient inclusion of the deaf into the decision-making in municipalities in the Republic of Lithuania. The singleness for the improvement of the situation in municipalities has been modelled on the base of the mentioned results by activating all budgetary and public organisations operating under the Board of Municipality as well as Administration.